Electrode material, cathode foil for electrolytic capacitor, and electrolytic capacitor

By forming an oxide layer on the smooth substrate and imparting a multi-layer structure containing metal and carbon, the problem of insufficient adhesion and contact resistance between the cathode foil and the solid electrolyte in the prior art is solved, and higher durability and lower resistance are achieved.

CN119604958APending Publication Date: 2025-03-11JAPAN CAPACITOR IND CO LTD
View PDF 26 Cites 0 Cited by

Patent Information

Application Number
CN202380055041.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-14
Filing Date
2023-07-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, the cathode foil of the solid-state electrolytic capacitor and the hybrid capacitor has insufficient in terms of adhesion with the solid-state electrolyte and contact resistance at the interface, resulting in durability and resistance problems.

Method used

An electrode material is used that forms an oxide layer on the smooth substrate and imparts a first conductive layer containing metal and/or metal compounds and a second conductive layer containing carbon on the oxide layer. The first conductive layer has an uneven portion, and the second conductive layer is located at the outermost layer of the inorganic conductive layer.

Benefits of technology

Good adhesion to solid electrolytes and low contact resistance are achieved, the durability and conductivity of the cathode foil are improved, the ESR of the capacitor is reduced, and the manufacturing cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604958A_ABST
    Figure CN119604958A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing: an electrode material or the like that can be used in a cathode foil or the like for an electrolytic capacitor, said electrode material having all of the following advantages: good adhesion to a solid electrolyte, and low contact resistance at an interface; having a layer (geometric structure, surface modification) for holding a solid electrolyte and electrolyte solution; the degradation resistance to a solid electrolyte, an electrolyte solution and moisture is excellent; the capacitor has no capacitance component or has a low capacitance component, and functions as a low-resistance conductor (no composite capacitance or low composite capacitance). The thinning can be realized; the cost is low; and coiling deviation is not easily caused. Provided is an electrode material which comprises an oxide layer on a smooth substrate and an inorganic conductive layer on the oxide layer, in which the inorganic conductive layer comprises a first conductive layer containing a metal and / or a metal compound and a second conductive layer containing carbon, the first conductive layer has an uneven portion on the surface layer side thereof, and the second conductive layer has an uneven portion on the surface layer side thereof. The second conductive layer is located on the outermost layer of the inorganic conductive layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrode material, and more particularly to a cathode foil for an electrolytic capacitor that can be used in an electrolytic capacitor such as a solid electrolytic capacitor and a hybrid capacitor, and an electrolytic capacitor. Background Art

[0002] The functions and characteristics required for the cathode of a hybrid capacitor include:

[0003] (i) Good adhesion to the solid electrolyte and low contact resistance at the interface;

[0004] (ii) having a layer for retaining a solid electrolyte or an electrolyte (geometric structure, surface modification);

[0005] (iii) Having resistance to degradation caused by solid electrolytes, chemical polymer solutions, electrolytes, and moisture;

[0006] (iv) having no capacitance component or having a low capacitance component and functioning as a low-resistance conductor;

[0007] (v) Thin layers can be achieved;

[0008] (vi) low cost; etc.

[0009] Apart from the compatibility with the electrolyte in (ii) and (iii) above, these can also be said to be extremely important functions and characteristics in the cathode for solid electrolytic capacitors.

[0010] In this regard, for example, a foil having a smooth titanium layer on a smooth foil and a smooth carbon layer on top thereof has insufficient adhesion to (i) a dispersion of a solid electrolyte, especially an aqueous solution as a dispersion medium, and poor retention of (ii) an electrolyte. In particular, for a solid electrolyte composed of a conductive polymer, it is difficult to maintain a healthy doping state, and when formed into an element, it becomes high resistance. In addition, since the foil thickness of the cathode foil formed by chemical etching is relatively thick, it is difficult to achieve miniaturization. When combined with an anode to form a capacitor, a synthetic capacitance is generated, which reduces the capacitance extraction rate of the anode. In addition, although the ESR (Equivalent Series Resistance) is low on the high-frequency side such as 100kHz, on the low-frequency side such as 120Hz, the ESR increases significantly and there is a narrow frequency range of low ESR. The part that has a large contact resistance with the solid electrolyte and is not covered with the solid electrolyte is also worrying about its low-temperature characteristics due to the dependence on the electrolyte. In addition, in the aging and forming step after the element is formed, the cathode foil may be partially formed, and there is a concern that the capacitance is reduced or the resistance is increased. For example, the chemical coating layer applied to the aluminum substrate has a certain protective function for the electrolyte. However, for the solid electrolyte composed of conductive polymers, it is difficult to completely suppress the chemical reaction with the acidic electrolyte used to maintain the doping state of the chemical polymerization solution or the solid electrolyte, or the chemical reaction between the slightly existing water and the substrate. On the other hand, when the natural oxide film or the chemical coating is in direct contact with the solid electrolyte in this state, there is a problem of increased contact resistance because a depletion layer will be generated at the contact interface.

[0011] In the foil after the intermediate layer (titanium layer) and then the carbon layer are given on the chemically etched foil, the thickness is relatively thin and the conductive polymer or electrolyte can be retained by the etching layer, but the titanium layer or carbon layer given to the etching layer is difficult to completely coat the inside of the etching layer. In order to protect it from the influence of the electrolyte or solid electrolyte, and the chemical polymerization solution, it is necessary to have an aluminum oxide layer (need to have a chemical coating of several V, for example). This chemical coating layer also has the function of protecting it from the influence of the electrolyte as mentioned above, but it will still function as an insulator when used directly, which is likely to cause high resistance. In addition, solid electrolytic capacitors in which there is no electrolyte in the middle and the electrolyte is only composed of solid electrolytes can also be said to meet most of these problems.

[0012] Various cathode foils used in electrolytic capacitors such as solid electrolytic capacitors and hybrid capacitors have been developed in the past. Patent documents 1 and 3 describe an electrolytic capacitor having an inorganic conductive layer formed on the surface of a cathode foil roughened by etching (surface expansion ratio 1.5 to 500 times). However, these cathode foils have the following problems:

[0013] When using an etching substrate after expanding a smooth substrate by etching, it is difficult for the material of the inorganic conductive layer to penetrate into the etching layer and it is difficult to completely cover the etching layer with the material of the inorganic conductive layer, so aluminum, which is a component of the substrate, will be exposed.

[0014] .There is a film of aluminum oxide on the surface of the exposed aluminum. Since aluminum oxide is an insulator, it has high resistance.

[0015] .The exposed aluminum has weak chemical resistance and has durability issues relative to polymers or electrolytes.

[0016] Since the base material is dissolved by etching, there are also major issues in terms of processing strength, thinning of foil, residual chlorine, waste liquid treatment, and manufacturing cost.

[0017] In addition, Patent Document 4 describes a cathode foil for aluminum electrolytic capacitors, characterized in that a first layer composed of at least one of a metal and its nitride, carbide, carbonitride, and oxide is formed on the surface of the aluminum foil, and a second layer composed of at least one of a metal and its nitride, carbide, carbonitride, and oxide is formed on the first layer, and the first layer has a denser structure than the second layer. However, the invention described in Patent Document 4 is mainly aimed at improving hydration resistance and uses a cathode for a capacitor that uses an electrolyte containing only water as an electrolyte. There is still room for improvement in terms of lowering the resistance and improving the durability of the cathode of an electrolytic capacitor that can be used in a hybrid capacitor, a solid electrolytic capacitor, etc.

[0018] Patent document 2 describes a cathode foil for a hybrid capacitor using a smooth substrate and having a carbon layer formed thereon. In addition, patent document 5 describes a cathode foil for a solid electrolytic capacitor using a smooth substrate and having carbon on a metal layer. However, since there are no concave-convex parts on the surface side of these cathode foils, it is believed that there is still room for further improvement in ESR or durability. In addition, since there are no concave-convex parts on the surface side of the cathode foil, the friction with the separator paper (isolation paper) is weak, and when the core fixture is pulled out in the element winding step of the electrolytic capacitor, it is easy to produce winding deviation loss in which the cathode foil flies in the direction of pulling out the core fixture.

[0019] Patent document 9 describes an electrolytic capacitor, which uses: a cathode comprising a plurality of metal particles having a median diameter of about 20 to about 500 microns arranged and sintered and bonded on the surface of a substrate, but the size of the micron unit is too large to obtain the geometric structure required to maintain the solid electrolyte and the electrolyte, and there is room for improvement. Other patent documents 6 to 8, 10 to 24 have been cited as prior art, but in any of them, it can be considered that there is still room for improvement in its function and performance.

[0020] [Prior art literature]

[0021] [Patent Document]

[0022] [Patent Document 1] International Publication No. 2016 / 174806

[0023] [Patent Document 2] International Publication No. 2016 / 174807

[0024] [Patent Document 3] International Publication No. 2016 / 189779

[0025] [Patent Document 4] Japanese Patent Application Publication No. 2014-022707

[0026] [Patent Document 5] Japanese Patent Application Publication No. 2012-174865

[0027] [Patent Document 6] Japanese Patent Application Publication No. 2023-002273

[0028] [Patent Document 7] International Publication No. 2017 / 090241

[0029] [Patent Document 8] Japanese Patent Application Publication No. 2019-179884

[0030] [Patent Document 9] Japanese Patent Application Publication No. 2007-243203

[0031] [Patent Document 10] Japanese Patent Application Publication No. 2015-073015

[0032] [Patent Document 11] Japanese Patent Application Publication No. 2019-179884

[0033] [Patent Document 12] U.S. Patent No. 10896783

[0034] [Patent Document 13] International Publication No. 2021 / 107063

[0035] [Patent Document 14] International Publication No. 2012 / 115050

[0036] [Patent Document 15] Japanese Patent Application Publication No. 2004-281223

[0037] [Patent Document 16] Japanese Patent Application Publication No. 2012-195527

[0038] [Patent Document 17] Japanese Patent Application Publication No. 2011-192924

[0039] [Patent Document 18] Japanese Patent Application Publication No. 2021-145135

[0040] [Patent Document 19] U.S. Patent Application Publication No. 2009 / 0161299

[0041] [Patent Document 20] European Patent Application Publication No. 3817020

[0042] [Patent Document 21] U.S. Patent Application Publication No. 2014 / 0036416

[0043] [Patent Document 22] U.S. Patent Application Publication No. 2021 / 0383981

[0044] [Patent Document 23] Japanese Patent Application Publication No. 2005-294500

[0045] [Patent Document 24] International Publication No. 2010 / 029598

[0046] [Patent Document 25] Japanese Patent Application Publication No. 2006-190878

[0047] [Patent Document 26] Japanese Patent Application Publication No. 2022-057601

[0048] [Patent Document 27] Japanese Patent Publication No. 2022-057985. Summary of the invention

[0049] [Problems to be solved by the invention]

[0050] In view of the above, the present invention aims to realize an electrode material that can be used in a cathode foil for an electrolytic capacitor, or an electrolytic capacitor having a cathode foil using the electrode material, wherein the cathode foil for an electrolytic capacitor has at least one of the following advantages (1) to (7):

[0051] (1) Good adhesion with solid electrolyte and low contact resistance at the interface;

[0052] (2) Having a layer for retaining solid electrolyte and electrolyte (geometric structure, surface modification);

[0053] (3) Excellent resistance to degradation by solid electrolytes, chemical polymer solutions, electrolytes, and water;

[0054] (4) It has no capacitance component or has a low capacitance component, and functions as a low-resistance conductor;

[0055] (5) Thin layers can be achieved;

[0056] (6) Low cost;

[0057] (7) It is not easy to cause winding deviation.

[0058] [Technical means to solve the problem]

[0059] In order to solve the above-mentioned problems, the present invention provides an electrode material, which has an oxide layer on a smooth substrate, and further has an inorganic conductive layer on the oxide layer, wherein the inorganic conductive layer has: a first conductive layer containing a metal and / or a metal compound and a second conductive layer containing carbon, wherein the first conductive layer has a concave-convex portion on its surface side, and the second conductive layer is located at the outermost layer of the inorganic conductive layer. An example of the so-called "smooth substrate" herein is a substrate that has not been subjected to a roughening treatment such as etching, but the surface of the substrate does not need to be completely smooth. The smooth substrate also includes a substrate having tiny roughness or undulations on the surface caused by unavoidable rolling streaks or scratches that are only slightly generated in a foil base manufacturing process such as rolling processing (of course, the surface of the substrate may also be completely smooth). In addition, the so-called "oxide layer" may be an oxide layer formed without special treatment like a natural oxide film, or may be an oxide layer intentionally formed by a treatment such as a chemical conversion treatment. The oxide layer may completely or partially cover the smooth substrate. For example, the smooth substrate may be in direct contact with the first conductive layer by allowing the material of the dense layer to penetrate the oxide layer portion in the first conductive layer (forming the dense layer by the arc ion plating (AIP) method described later). In addition, when the second conductive layer is formed on the concave-convex portion of the first conductive layer, the second conductive layer may be divided into a plurality of portions due to the shape of the concave-convex portion (see the embodiment described later). Figure 1 However, the so-called "layer" in the above description and the following description may also be a "layer" formed by dividing into a plurality of parts in this way (not limited to the second conductive layer, the same applies to any layer).

[0060] The smooth substrate and the first conductive layer may be made of different materials.

[0061] The second conductive layer may be a layer consisting essentially of carbon.

[0062] In addition, in the above description, the so-called "substantially composed of carbon" or "composed of carbon" does not necessarily mean that the material constituting the second conductive layer does not contain any component other than carbon. Due to the control of the purity of the components in the layer, the limitations of the manufacturing technology regarding the mixing of impurities, or the tolerance of the allowable error of the above-mentioned electrode material in individual products, the actual composition of the components will vary in various ways (as long as the function of the electrode material is maintained within the allowable range, the second conductive layer may contain components other than carbon). This point is also the same as the descriptions such as "substantially composed of", "composed of", "substantially only contains", "only contains".

[0063] The inorganic conductive layer may further include a dense layer in which the metal and / or metal compound is densely present, and the dense layer may also be formed between the oxide layer and the first conductive layer. Here, "densely present" means that (the metal and / or metal compound) is more densely present than the above-mentioned "concave and convex part".

[0064] In the inorganic conductive layer, both the first conductive layer and the second conductive layer or at least the first conductive layer may be a layer composed of a particle deposition layer, and the first conductive layer may be a layer containing at least one of titanium, aluminum, nitrides, oxides, oxynitrides, carbides, and carbonitrides thereof. The materials that can be used in the first conductive layer are not limited to these, but when an aluminum substrate is used as the substrate, from the viewpoint of energy efficiency or adhesion to the aluminum substrate, it is particularly preferred to use a metal headed by titanium (Ti) and aluminum (Al) (as long as the adhesion to the substrate or the conductivity in the first conductive layer is not impaired, a metal containing multiple components such as an alloy may also be used).

[0065] The oxide layer may also be an oxide layer containing phosphorus.

[0066] The smooth substrate may be a substrate containing aluminum or an aluminum alloy. In addition, the material that can be used as the substrate is not limited to aluminum, and any other material such as tantalum (Ta), titanium (Ti), niobium (Nb), hafnium (Hf), zirconium (Zr), zinc (Zn), tungsten (W) and the like, which are valve metals, or an aluminum alloy in which any of these materials are added to aluminum, etc. may be used.

[0067] The maximum current value of the cyclic voltammogram obtained by cyclic voltammetry under the conditions of a scan range of ±0.3VvsPt, a scan rate of 500mV / sec, an electrolyte at 30°C, a reference electrode of Pt, a relative electrode of stainless steel, and the aforementioned electrode material as a working electrode is more than 6.5 times the maximum current value of the cyclic voltammogram when the aforementioned smooth substrate is used as a working electrode under the aforementioned conditions.

[0068] Between the first conductive layer and the second conductive layer, a mixed layer in which the substance constituting the first conductive layer and the substance constituting the second conductive layer are mixed can be formed, and the composition of the mixed layer can be configured such that as it moves from the first conductive layer toward the second conductive layer, the composition substantially only contains the substance constituting the first conductive layer and the composition substantially only contains the substance constituting the second conductive layer. As previously described, the phrases "substantially only contain the substance constituting the first conductive layer" and "only contain the substance constituting the first conductive layer" do not necessarily mean that the composition does not contain any other component than the "substance constituting the first conductive layer", and the phrases "substantially only contain the substance constituting the second conductive layer" and "only contain the substance constituting the second conductive layer" do not necessarily mean that the composition does not contain any other component than the "substance constituting the second conductive layer" (other components may be contained within a range where the function of the electrode material is maintained to an acceptable degree).

[0069] In addition, in the above description, the so-called "as it moves from the first conductive layer toward the second conductive layer, the composition substantially only contains the substance constituting the first conductive layer to the composition substantially only contains the substance constituting the second conductive layer" does not necessarily mean that the content of the substance constituting the second conductive layer in the mixed layer increases monotonically from the first conductive layer toward the second conductive layer. The actual composition at each position in the mixed layer may change in various ways in accordance with the changes in the concentration of each component caused by the limitations of the manufacturing technology. However, it is preferred to form the mixed layer in such a way that the content of the substance constituting the second conductive layer continuously increases from the first conductive layer toward the second conductive layer.

[0070] Between the first conductive layer and the second conductive layer, a mixed layer in which a substance constituting the first conductive layer and a substance constituting the second conductive layer are mixed can be formed, and the composition of the mixed layer can be composed as follows: as it moves from the first conductive layer toward the second conductive layer, the composition substantially contains only the substance constituting the first conductive layer to the composition substantially contains only the substance constituting the second conductive layer; when analyzing the amount of each C bonding state from the surface of the second conductive layer toward the depth direction by XPS (X-ray photoelectron spectroscopy), the ratio of the amount of bonding between atoms of the metal element constituting the first conductive layer and carbon atoms to the total amount of each C bonding state shown by the C1s spectrum can be 5% or more.

[0071] Regarding the half-value width of the G band peak obtained by peak separation in a Raman spectrum formed by Raman spectroscopy, the half-value width of carbon contained in the second conductive layer can be 3.8 times or more relative to the half-value width of graphite crystal.

[0072] The material constituting the first conductive layer and the material constituting the second conductive layer may be different from each other.

[0073] The BET specific surface area using krypton (Kr) as the adsorption gas can be 1.5 times or more of the BET specific surface area of ​​the smooth substrate.

[0074] The average diameter of the convex portions of the concavo-convex portion on the surface layer side of the inorganic conductive layer can be 210 nm or less.

[0075] The carbon may be graphite-like carbon.

[0076] There is no particular limitation on the type of carbon material used. Among carbon materials, graphite-like carbon having excellent conductivity is particularly preferred in terms of reducing the ESR of electrolytic capacitors. In addition, it is also preferred in terms of manufacturing cost. The so-called graphite-like carbon herein refers to a carbon having a diamond bond (sp bond between carbon atoms). 3 Hybrid orbital bonding) and graphite bonding (sp 2 In the amorphous carbon structure where both sp and sp bonds exist, the ratio of graphite bonds exceeds 50% (the number of graphite bonds is greater than the number of diamond bonds). However, in addition to the amorphous structure, there are also crystalline structures that are partially composed of graphite structures (that is, sp 2 The sp 3 Bonding and sp 2 The ratio of the bonding state can be analyzed by Raman spectroscopy or XPS (X-ray photoelectron spectroscopy (also known as ESCA)).

[0077] In the electrode material of one embodiment of the present invention, the static friction coefficient and dynamic friction coefficient of the surface side surface against the separator paper can be respectively higher than: the static friction coefficient and dynamic friction coefficient of the surface side surface of the electrode material having a conductive layer composed of carbon as the outermost layer on the surface side on a smooth substrate and no concave-convex parts on the surface side.

[0078] The present invention also provides a cathode foil for an electrolytic capacitor in which at least a solid electrolyte is present between an anode foil and a cathode foil, and the cathode foil uses the electrode material of the present invention.

[0079] In addition, the present invention provides an electrolytic capacitor, wherein at least a solid electrolyte exists between an anode foil and a cathode foil, and the electrolytic capacitor has the cathode foil of the present invention. In one example, a solid electrolytic capacitor is provided.

[0080] The electrolytic capacitor may be an electrolytic capacitor with an electrolyte between the anode foil and the cathode foil. In one example, a hybrid capacitor is provided.

[0081] [Effects of the Invention]

[0082] The present invention provides an electrode material that can be used in a cathode foil for an electrolytic capacitor, or an electrolytic capacitor having a cathode foil using the electrode material, wherein the cathode foil for an electrolytic capacitor has at least one of the advantages (1) to (7) listed in the problems to be solved by the invention. Specifically, for example, the following is described.

[0083] . Since a smooth foil is used instead of an etching substrate, there is no need to worry about residual chlorine, and there is no situation where the inorganic conductive layer material is difficult to penetrate into the etching layer, resulting in the aluminum being exposed. Therefore, the degradation resistance (drug resistance, durability) to solid electrolytes, chemical polymer solutions, electrolytes, and water can be improved ((3)), and the strength can be maintained while achieving thinning ((5)). In addition, since the etching step can be removed, problems including waste liquid equipment can be reduced, and costs can be reduced ((6)).

[0084] In one example, an inorganic conductive layer having concave-convex portions is applied to the surface side of a smooth foil by vapor deposition, thereby providing a layer having a geometric structure suitable for retaining a solid electrolyte and an electrolyte solution ((2)).

[0085] .By imparting a geometric concave-convex structure to the surface side, the adhesion with the solid electrolyte is improved ((1)).

[0086] .By imparting a geometric concave-convex structure to the surface layer side, the static and dynamic friction forces (each friction coefficient) with the separator paper are increased, thereby suppressing the winding deviation defect ((7)) that is easily produced when the core fixture is pulled out during the element winding step of the electrolytic capacitor.

[0087] .By providing a layer containing carbon as the outermost layer of the inorganic conductive layer, a cathode foil having low resistance and no capacitance component can be formed (by forming a first conductive layer containing a metal and / or a metal compound and a second conductive layer containing carbon on the aluminum oxide layer, the formation of a depletion layer caused by contact with a solid electrolyte, such as an aluminum oxide film, is suppressed, thereby significantly reducing the contact resistance with the solid electrolyte) ((1) and (4)). BRIEF DESCRIPTION OF THE DRAWINGS

[0088] Figure 1 This is a cross-sectional view showing the layer structure of a cathode foil using an electrode material according to one embodiment of the present invention.

[0089] Figure 2 This is a cross-sectional view showing the layer structure of a cathode foil using an electrode material according to one embodiment of the present invention (Variation 1).

[0090] Figure 3 This is a cross-sectional view showing the layer structure of a cathode foil using an electrode material according to one embodiment of the present invention (Variation 2).

[0091] Figure 4 This is a cross-sectional view showing the layer structure of a cathode foil using an electrode material according to one embodiment of the present invention (Variation 3).

[0092] Figure 5 To show an embodiment of the present invention, using Figure 1 A cross-sectional view of a layer structure of a cathode foil in which each layer of electrode material is laminated only on one side of a substrate.

[0093] Figure 6 To show an embodiment of the present invention, using Figure 2 A cross-sectional view of a layer structure of a cathode foil in which each layer of electrode material is laminated only on one side of a substrate.

[0094] Figure 7 To show an embodiment of the present invention, using Figure 3 A cross-sectional view of a layer structure of a cathode foil in which each layer of electrode material is laminated only on one side of a substrate.

[0095] Figure 8 To show an embodiment of the present invention, using Figure 4 A cross-sectional view of a layer structure of a cathode foil in which each layer of electrode material is laminated only on one side of a substrate.

[0096] Fig. 9 This is an exploded view showing the structure of a wound solid electrolytic capacitor and a wound hybrid capacitor according to one embodiment of the present invention.

[0097] Fig.10 This is a TEM (Transmission Electron Microscopy) photograph (cross-sectional image) of a cathode foil (Example 2 described later) using an electrode material according to one embodiment of the present invention.

[0098] Fig.11 This is a TEM photograph (cross-sectional image) of a cathode foil (Example 4 described later) using an electrode material according to another embodiment of the present invention.

[0099] Fig.12 For Fig.10 A STEM (Scanning Transmission Electron Microscopy) photograph (cross-sectional image) of the same cathode foil (Example 2).

[0100] Fig.13 For Fig.11 STEM photograph (cross-sectional image) of the same cathode foil (Example 4).

[0101] Fig.14 For Fig.10 TEM images (bright field image, cross-sectional image) of the same cathode foil (Example 2).

[0102] Fig.15 For Fig.11 TEM images (bright field image, cross-sectional image) of the same cathode foil (Example 4).

[0103] Fig.16 To display and Fig.10 A graph showing the analysis results of the same cathode foil (Example 2) measured by ToF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry) (showing the cross-sectional distribution of the chemical bonding state).

[0104] Fig.17 To display and Fig.11 A graph showing the analysis results of the same cathode foil (Example 4) measured by ToF-SIMS (showing the cross-sectional distribution of the chemical bonding state).

[0105] Fig.18 To display and Fig.10 , Fig.11 Graph of Raman scattering spectra (full wave number region) of the same cathode foils (Examples 2 and 4) measured by laser micro-Raman spectroscopy.

[0106] Fig.19 To display and Fig.10 , Fig.11 Graph of Raman scattering spectra (CC bond region) of the same cathode foils (Examples 2 and 4) measured by laser micro-Raman spectroscopy.

[0107] Fig. 20 This is a table showing the results of ESR measurement of Examples 1 to 11 of the hybrid capacitor and Comparative Examples 1 to 3 of the hybrid capacitor.

[0108] Fig.21 1 is a table showing the results of ESR measurement of Examples 1 to 11 of the solid electrolytic capacitors and Comparative Examples 1 to 3 of the solid electrolytic capacitors.

[0109] Fig. 22 To display and Fig.10The cross-sectional distribution of elements of the same cathode foil (Example 2) measured by TEM-EDS (Transmission Electron Microscopy-Energy Dispersive X-ray Spectroscopy).

[0110] Fig.23 To display and Fig.11 The cross-sectional distribution of elements of the same cathode foil (Example 4) measured by TEM-EDS.

[0111] Fig.24 To display and Fig.10 The cross-sectional distribution of elements of the same cathode foil (Example 2) measured by STEM-EELS (Scanning Transmission Electron Microscopy-Electron Energy Loss Spectroscopy) (compared to Fig.25 is located on the carbon conductive layer side).

[0112] Fig.25 To display and Fig.10 The cross-sectional distribution of elements measured by STEM-EELS of the same cathode foil (Example 2) ( Fig.24 is located on the substrate side).

[0113] Fig.26 To display and Fig.11 The cross-sectional distribution of elements measured by STEM-EELS of the same cathode foil (Example 4) ( Fig. 27 is located on the carbon conductive layer side).

[0114] Fig. 27 To display and Fig.11 The cross-sectional distribution of elements measured by STEM-EELS of the same cathode foil (Example 4) ( Fig.26 is located on the substrate side).

[0115] Fig.28 TABLE 1 is a table showing the results of a tape bonding test conducted on the cathode foils of Examples 1, 2, 4, and 5 and the cathode foil of Comparative Example 1.

[0116] Fig.29 To show the Fig.10 , Fig.11 The table shows the contact angle measurement results of the same cathode foils (Examples 2 and 4) and the cathode foil of Comparative Example 1, and the content of the surface free energy (hydrogen bonding component and dispersion force component) calculated therefrom.

[0117] Fig.30 Part a) is related to Fig.10 SEM (Scanning Electron Microscopy) photo (surface image) of the same cathode foil (Example 2); b) part is Fig.11 The SEM photograph (surface image) of the same cathode foil (Example 4); part c) is the SEM photograph (surface image) of the cathode foil of Example 5; part d) is the SEM photograph (surface image) of the cathode foil of Example 6.

[0118] Fig.31 TABLE 2 is a table showing the average diameters (Feret's Diameter) of Examples 1 to 6 and 8.

[0119] Fig.32 Part a) shows the Fig.10 The graph of the amount of each element in the depth direction measured by XPS (X-ray photoelectron spectroscopy) of the same cathode foil (Example 2); part b) shows the difference between the cathode foil and the cathode foil. Fig.10 This is a graph showing the total amount of each C bonding state and the amount of TiC bonds in the depth direction measured by XPS for the same cathode foil (Example 2).

[0120] Fig.33 To display and Fig.10 , Fig.11 Narrow scan spectra due to C bonding states obtained by XPS for the same cathode foils (Examples 2 and 4).

[0121] Fig.34 TABLE 2 is a table showing the static friction coefficient and the average dynamic friction coefficient of the cathode foils of Examples 2, 4, and 5 and the cathode foil of Comparative Example 1.

[0122] Fig.35 To display and Fig.10 This is a diagram showing the separation of the G band peak from the spectrum measured by Raman spectroscopy of the same cathode foil (Example 2).

[0123] Fig.36 This is a table showing the ratios of the BET specific surface area of ​​the cathode foils of Examples 1 to 8 measured by the Kr adsorption method to the BET specific surface area of ​​the smooth substrate. DETAILED DESCRIPTION

[0124] The following describes a cathode foil for an electrolytic capacitor using an electrode material and an electrolytic capacitor using the cathode foil as an embodiment of the present invention. However, as described, the aluminum foil used as the substrate in the following description, and the titanium (Ti) or aluminum (Al) used to form the first conductive layer, can also be replaced by other materials. For example, the material used to form the first conductive layer can be listed as: a material containing any of tantalum (Ta), titanium (Ti), chromium (Cr), aluminum (Al), niobium (Nb), vanadium (V), tungsten (W), hafnium (Hf), copper (Cu), zirconium (Zr), zinc (Zn), nitrides of these metals, oxides of these metals, oxynitrides of these metals, carbides of these metals, and carbonitrides of these metals (the first conductive layer may contain any material other than these; the same applies to other layers). Carbon is not limited to graphite-like carbon, and can be any carbon material. In addition, the use of the electrode material of the present invention is not limited to cathode foil for solid electrolytic capacitors or hybrid capacitors, and the electrode material can be used in electrodes (cathode, anode, positive electrode, negative electrode, etc.) of any storage element such as other secondary batteries, electric double layer capacitors, lithium ion capacitors, etc. The electrolytic capacitor of the present invention is not limited to the wound electrolytic capacitor described later, and can be any type such as a stacked type, a chip type, etc. Figure 1 The concavo-convex part of the first conductive layer shown in the above does not need to be formed on the entire surface of the first conductive layer, and the concavo-convex part may be only partially provided on the surface of the first conductive layer (of course, the concavo-convex part may also be formed on the entire surface of the first conductive layer). Figure 1 The "smooth" substrate mentioned in the above does not necessarily have to be smooth on the entire surface. For example, in the foil base manufacturing process such as rolling, the substrate with slight roughness or undulations on the surface caused by unavoidable rolling streaks or scratches that are only slightly generated is also included in the "smooth substrate" (of course, in the case of a smooth substrate, the substrate surface may also be completely smooth). Figure 1 The "second conductive layer" described in the above description may be a layer (substantially) composed only of carbon, or may be a layer containing other components besides carbon, such as tantalum (Ta), titanium (Ti), chromium (Cr), aluminum (Al), niobium (Nb), vanadium (V), tungsten (W), hafnium (Hf), copper (Cu), zirconium (Zr), zinc (Zn), and any of the nitrides of these metals, the oxides of these metals, the oxynitrides of these metals, the carbides of these metals, and the carbonitrides of these metals. The carbon content in the second conductive layer may be any content. In addition, the electrode material, cathode foil for electrolytic capacitor, or electrolytic capacitor of the present invention need not completely possess all the layers or constituent elements and structures described in the following embodiments, and the electrode material and cathode foil for electrolytic capacitor may not have any one or more layers at least in the dense layer or the mixed layer. As described later Figure 1In the invention, a first conductive layer is formed on both sides of a smooth substrate, but various layers or elements such as concave-convex parts can be arranged only on one side of the smooth substrate or on both sides. In addition, an oxide layer can be arranged on the first side (surface of the surface side) of the smooth substrate but not on the second side (inner side), so that different layer structures are arranged on the first side and the second side of the substrate, and the presence or absence or configuration of elements such as concave-convex parts are also different from the present invention on one side, to form an electrode material or an electrolytic capacitor having a cathode foil using an electrode material. As for other layers or elements, structures, features, etc., as long as the electrode material, cathode foil for electrolytic capacitor or electrolytic capacitor of the present invention can function, they can be appropriately omitted. In addition, as long as the electrode material or electrolytic capacitor of the present invention can function, the electrode material, cathode foil for electrolytic capacitor or electrolytic capacitor of the present invention can also have layers, elements, structures, features other than the layers, elements, structures, features described in the following embodiments. In addition, in the electrolytic capacitor of the present invention, any electrode material in the electrode material of the present invention can be used as the cathode foil. The various layers, elements, structures, features, etc. described above can be arbitrarily selected and appropriately combined, and the electrode materials, cathode foils for electrolytic capacitors, electrolytic capacitors, etc. obtained by such selection and combination are all included in the scope of the present invention.

[0125] In addition, the above-mentioned resistance to degradation by solid electrolytes, chemical polymerization solutions, electrolyte solutions and water can be further improved by taking the following measures.

[0126] .When the adhesion between the interface of the smooth foil and the vapor-deposited layer is insufficient, the vapor-deposited layer can be applied after being coated with a dense inorganic conductive layer. In one example, coating the smooth foil with a dense inorganic conductive layer can completely eliminate the exposed portion of aluminum and improve chemical resistance and durability.

[0127] .After imparting an oxide film containing phosphorus (P) to a smooth foil, coating it with a dense inorganic conductive layer can further improve chemical resistance and durability (even when a dense layer is not formed, chemical resistance and durability can be improved by imparting an oxide film containing phosphorus to a smooth substrate through chemical conversion treatment, etc.

[0128] Durability).

[0129] Cathode foil using the electrode material of the present invention

[0130] Figure 1This is a cross-sectional view showing the layer structure of a cathode foil using an electrode material according to one embodiment of the present invention. The cathode foil (electrode material) 1 includes: a substrate (smooth aluminum foil) 2 that has not been roughened by etching or the like, an oxide layer 3 such as a natural oxide film or an artificially formed oxide film containing phosphorus formed on the smooth aluminum foil 2, a first conductive layer 4 having irregularities formed on the oxide layer 3 and made of Ti or Al, and a second conductive layer 5 formed on the first conductive layer 4.

[0131] A commercially available high-purity aluminum sheet can be used as the smooth aluminum foil 2. The thickness of the aluminum sheet is not particularly limited, but is preferably 10 μm to 50 μm when used as a cathode foil for a wound electrolytic capacitor (solid electrolytic capacitor, hybrid capacitor, etc.).

[0132] The oxide layer 3 is a natural oxide film or an oxide layer such as an oxide film intentionally formed by a chemical treatment such as anodization or immersion treatment containing phosphorus, and can be formed by exposing the smooth aluminum foil 2 to the air, or performing an anodization treatment using an ammonium dihydrogen phosphate solution, or immersing it in an aqueous phosphoric acid solution or an aluminum dihydrogen phosphate aqueous solution and then performing a heat treatment.

[0133] In one example, the first conductive layer 4 is formed in a vacuum treatment chamber by arranging: a smooth aluminum foil 2 having an oxide layer 3 formed thereon, or a smooth aluminum foil 2 having a dense layer 6 formed thereon by arc ion plating or the like in the case of forming an optional dense layer 6 described later, and a metal material of Ti or Al as an evaporation source, and then evaporating the metal material and attaching the evaporated metal material to the oxide layer 3 (on the dense layer 6 when forming the dense layer 6) (evaporation method). In addition to the above-mentioned vacuum evaporation method, the evaporation method can use a chemical vapor deposition (CVD: Chemical Vapor Deposition) method, a sputtering method, etc., and in terms of the control of the geometric structure, an electron beam evaporation method is also preferred in the vacuum evaporation method. The electron beam evaporation method is a method of irradiating an accelerated electron beam on a vaporized material to heat and vaporize it, and then depositing it on a substrate. The fineness of the concavities and convexities in the first conductive layer can be controlled by, for example, adjusting the particle size of the attached metal material. In the evaporation, the particle size of the metal material can be appropriately controlled by adjusting conditions such as the type of introduced gas or the degree of vacuum, the temperature of the substrate, etc. In addition, in the scheme of forming the first conductive layer 4 composed of nitride, oxide or carbide of metals such as Ti or Al on the smooth aluminum foil 2 on which the oxide layer 3 is formed and the dense layer 6 is further formed when the dense layer 6 is formed, it is only necessary to form the first conductive layer 4 by performing the above method in an environment such as nitrogen, oxygen, or a hydrocarbon gas such as acetylene gas or methane gas. In addition, in the scheme of forming the first conductive layer 4 composed of oxynitride or carbonitride of metals such as Ti or Al, it is only necessary to form the first conductive layer 4 in an environment such as nitrogen and oxygen, or nitrogen and a hydrocarbon gas such as acetylene gas or methane gas.

[0134] The second conductive layer 5 is preferably formed by a vapor deposition method such as an ion plating method rather than by dispersing carbon particles in a binder such as a resin adhesive and then applying the dispersed carbon particles. This is because in the layer of carbon particles formed by kneading with the binder, the carbon occupancy rate is reduced due to the amount of binder actually mixed, and the contact between the material of the first conductive layer in the lower layer and the carbon particles becomes a point contact, and it is also difficult to form a mixed layer. In addition, it is difficult to improve the conductivity of the interface in the above-mentioned coating method, the interface resistance increases, the adhesion also deteriorates, and it is difficult to coat thinly and uniformly. The second conductive layer 5 is preferably formed by a smooth and dense GLC (Graphite-Like Carbon: graphite-like carbon) coating. In addition, the carbon is measured by Raman spectroscopy and the G band peak (sp 2The larger the half-peak width obtained by separating the second conductive layer 5 (bonding part), the higher the degree of amorphism. Generally speaking, its density, hardness, Young's modulus, etc. will increase. Therefore, it is preferred to set the half-peak width of the carbon used in the second conductive layer 5 to be 3.8 times or more of the half-peak width of crystalline graphite. Accordingly, the degree of amorphism of the second conductive layer 5 is improved, and it becomes a film with excellent resistance to degradation (drug resistance and durability) with respect to solid electrolytes, chemical polymerization solutions, electrolytes and water. In addition, in the case where the second conductive layer 5 is formed on the concave and convex parts of the first conductive layer 4, since the shape of the second conductive layer 5 depends on the shape of the concave and convex parts of the first conductive layer 4, the second conductive layer 5 does not necessarily need to have concave and convex parts (the thickness is substantially constant), and can also be a smooth and dense coating. Figures 1 to 8 As shown, by making the surface side of the electrode material 1 have projections and depressions (but the surface projections and depressions are not necessary in the electrode material 1), it can be considered that the static friction coefficient and dynamic friction coefficient of the surface side of the electrode material 1 with respect to the separator paper are higher than the static friction coefficient and dynamic friction coefficient of the surface side of the electrode material with respect to the separator paper, which has a conductive layer composed of carbon as the outermost layer on the surface side on a smooth substrate and has no projections and depressions on the surface side.

[0135] The second conductive layer 5 is obtained by the same method as the dense layer 6, and among them, the ion plating method such as the arc ion plating method with high ionization rate and adhesion energy of the film-forming material is one of the preferred methods because it is easy to form a mutual diffusion state with the first conductive layer and has a high effect of reducing the interface resistance. Specifically, in a vacuum processing chamber, after configuring: a stacked body having an oxide layer 3 and a first conductive layer 4 formed on a smooth aluminum foil 2 (a dense layer 6 is further formed between the oxide layer 3 and the first conductive layer 4 when forming the dense layer 6), and a carbon material as an evaporation source (as one example, a graphite material when forming the second conductive layer 5 as a GLC coating), a vacuum arc discharge is generated between the evaporation source target as a cathode and an anode, thereby evaporating and ionizing the carbon material, and then the carbon cations generated thereby are guided to the stacked body to form. Arc ion plating can locally generate high Joule heat caused by arc current on the target material in the formation of high melting point compound films such as carbides or nitrides, and because the plasma density is high, the ionization rate of the evaporated film-forming material can be increased, so it is more suitable. At this time, in order to accelerate the carbon cations toward the stack, a negative bias voltage can also be applied to the stack. When the concave-convex geometric shape is given to the second conductive layer 5, the same electron beam evaporation method as the concave-convex part of the first conductive layer 4 can also be used to introduce carbon materials (as one of the examples, when the second conductive layer 5 is formed as a GLC coating, it is a graphite material). The second conductive layer 5 can also contain any component other than carbon. When forming the second conductive layer 5 containing components other than carbon, it is only necessary to prepare any other material as an evaporation source in addition to the carbon material, and not only the carbon material, but also the other material is evaporated and ionized in the same way and guided to the stack.

[0136] Figure 2 This is a cross-sectional view showing the layer structure of a cathode foil using an electrode material according to one embodiment of the present invention (Variation 1). Figure 1 The layer structure is different, and a dense layer 6 is formed between the oxide layer 3 and the first conductive layer 4.

[0137] The dense layer 6 is formed by placing a smooth aluminum foil 2 having an oxide layer 3 formed thereon and a metal material of Ti or Al as an evaporation source in a vacuum treatment chamber, evaporating and ionizing Ti or Al by an electron beam and a plasma generating electrode, and guiding the metal cations ionized by arc discharge generated thereby to the smooth aluminum foil 2. At this time, in order to accelerate the metal cations toward the smooth aluminum foil 2, a negative bias voltage may be applied to the smooth aluminum foil 2. Therefore, the Ti or Al ions penetrate the oxide layer 3 formed on the surface of the smooth aluminum foil 2 and firmly adhere to the smooth aluminum foil 2. However, it is not necessary to penetrate the oxide layer 3 so that the material of the first conductive layer 4 is closely attached to the smooth aluminum foil 2. The oxide layer 3 may be a natural oxide film or an oxide film formed by an anodic oxidation treatment containing phosphorus, and may exist without holes between the first conductive layer 4 and the smooth aluminum foil 2. In addition, in the scheme of forming a dense layer 6 composed of a nitride, oxide or carbide of a metal such as Ti or Al on the smooth aluminum foil 2 formed with the oxide layer 3, it is sufficient to form the dense layer 6 by performing the above method in an environment of, for example, nitrogen, oxygen, or a hydrocarbon gas such as acetylene gas or methane gas. In addition, in the scheme of forming a dense layer 6 composed of a nitride oxide or carbonitride of a metal such as Ti or Al, it is sufficient to form the dense layer 6 in an environment of, for example, nitrogen and oxygen, or nitrogen and a hydrocarbon gas such as acetylene gas or methane gas.

[0138] In addition, the method for forming the dense layer 6 may be a vacuum evaporation method, a chemical vapor deposition method, a sputtering method, an atomic layer deposition method, a sol-gel method, a plating method, a coating method, a printing method, etc., in addition to an ion plating method such as an arc ion plating method. In one example, the ion plating method may be used from the point of view that the dense layer 6 and the smooth aluminum foil 2 penetrate the oxide layer 3 to firmly adhere to each other so that the ESR of the capacitor is suppressed to be low, and that a smooth metal film can be easily formed.

[0139] Figure 3 This is a cross-sectional view showing the layer structure of a cathode foil using an electrode material according to one embodiment of the present invention (Variation 2). Figure 1 The layer structure is different in that a mixed layer 7 is formed between the first conductive layer 4 and the second conductive layer 5 .

[0140] In one example, the mixed layer 7 is formed by performing two steps in a manner that the step of forming the first conductive layer 4 by a vapor deposition method such as a vacuum vapor deposition method and the step of forming the second conductive layer 5 by an arc ion plating method as described above are not completely separated in time, and the time for simultaneously performing the step of forming the first conductive layer 4 and the step of forming the second conductive layer 5 is generated. By introducing this mixed layer 7, the adhesion and chemical stability of the substance constituting the first conductive layer 4 (any substance containing a metal or a nitride, oxide, oxynitride, carbide or carbonitride of the metal as described above) and the substance constituting the second conductive layer 5 (carbon such as GLC, and any other substance contained in the second conductive layer 5 when the second conductive layer 5 also contains a material other than carbon) are improved, and deterioration caused by chemical reaction of the metal is prevented.

[0141] In addition, the mixed layer 7 is preferably formed in such a manner that it substantially contains only the substance constituting the first conductive layer 4 in the boundary region with the first conductive layer 4, and substantially contains only the substance constituting the second conductive layer 5 in the boundary region with the second conductive layer 5, and the content of the substance constituting the second conductive layer 5 continuously increases as it moves from the first conductive layer 4 toward the second conductive layer 5. In one example, the mixed layer 7 can be formed by performing the following (i) to (iii).

[0142] (i) When the formation of the mixed layer 7 begins, only the vapor deposition method that is a step of forming the first conductive layer 4 is performed, and the carbon material such as the graphite material (and any other material of the second conductive layer 5 when the second conductive layer 5 also contains a material other than carbon) is not irradiated with an electron beam;

[0143] (ii) gradually reducing the electron beam irradiation amount of the material constituting the first conductive layer 4 as time passes, thereby reducing the evaporation amount of the metal material in the vapor deposition method that is a step of forming the first conductive layer 4, and increasing the electron beam irradiation amount of the carbon material such as the graphite material (and any other material of the second conductive layer 5 when the second conductive layer 5 also contains a material other than carbon), thereby forming a mixed film in which the substance constituting the first conductive layer 4 and the substance constituting the second conductive layer 5 are mixed, and the content of the substance constituting the second conductive layer 5 increases toward the upper layer;

[0144] (iii) When film formation is completed, the vapor deposition method as the step of forming the first conductive layer 4 is terminated, and only the arc ion plating method as the step of forming the second conductive layer 5 is performed, thereby forming a film substantially composed of only the material constituting the second conductive layer.

[0145] Furthermore, in the case where the mixed layer 7 is formed by the vapor deposition method (first conductive layer 4) and the sputtering method (second conductive layer 5), the mixed layer 7 of the preferred embodiment can be formed by any method such as reducing the evaporation amount of the material of the first conductive layer 4 over time and increasing the voltage applied to the carbon target such as the graphite target (and when the second conductive layer 5 also contains a material other than carbon, any other target of the material of the second conductive layer 5) (increasing the sputtering speed of the graphite target and, when used, also increasing the target of the material of the other second conductive layer). In addition, (i) to (iii) are mainly suitable for single-wafer processing in a batch method, or alternatively, the mixed layer can be formed by a roll-to-roll method in which a target of a material constituting the first conductive layer and then a target of a material constituting the second conductive layer are sequentially arranged in a processing chamber, and a continuous film formation process is performed in sequence from the first to the second while conveying the foil. In addition, the first and second evaporation source targets are arranged adjacent to each other to form a mixed layer in such a way that the vapors or ions of the evaporation materials radiated conically from the first and second evaporation source targets toward the substrate blend with each other (contact) before reaching the substrate. By appropriately controlling the distance between the evaporation source targets or the distance between the evaporation source targets and the substrate, the mixed existence and diffusion state or bonding state of the mixed layer are adjusted to the optimal state. In this case, the amount of electron beam irradiation can be maintained at a constant level instead of being adjusted as described above, which can be considered a process more suitable for mass production. In addition, regardless of the distance between the evaporation source targets or the distance between the evaporation source targets and the substrate, a mixed layer can be obtained by heating the substrate temperature to, for example, several hundred degrees Celsius.

[0146] Figure 4 This is a cross-sectional view showing the layer structure of a cathode foil using an electrode material according to one embodiment of the present invention (Variation 3). Figure 1 The layer structure is different, a dense layer 6 is formed between the oxide layer 3 and the first conductive layer 4, and a mixed layer 7 is formed between the first conductive layer 4 and the second conductive layer 5.

[0147] In addition, as already explained, it is not necessary to Figures 1 to 4 As shown in FIG. 1 , each layer is stacked on both sides of the substrate 2, and the Figures 5 to 8 Generally, each layer is stacked only on one side of the substrate 2, but each layer can also be stacked on one side of the substrate 2. Figure 5 The layers shown are stacked on the other side of the substrate 2 Figure 6 The layers shown have different layer structures on the front side and the back side of the substrate 2 .

[0148] In addition, the thickness of the oxide layer 3, the dense layer 6, the first conductive layer 4, the mixed layer 7 and the second conductive layer 5 is sufficient to be about 0.005 μm or more and 1 μm or less, and if the total thickness of each layer except the substrate 2 is at least 0.05 μm or more on one side of the substrate 2, good characteristics as a cathode foil can be obtained. However, each layer may be formed thicker or thinner. Figures 1 to 8 The thickness of each layer is just an example, and the thickness of each layer can be determined arbitrarily.

[0149] As an index of the retention of a solid electrolyte or electrolyte, it is important to define the actual surface area of ​​the electrode material 1 by the BET specific surface area method of adsorbing nitrogen or krypton, but in one embodiment of the present invention, the electrochemical effective surface area after taking into account the ease of electricity flow such as the interface resistance which is important when forming an actual capacitor is obtained first, so it is evaluated by cyclic voltammetry. When 1M tetraethylammonium hexafluorophosphate using propylene carbonate as a solvent is used as an electrolyte, a Pt electrode is used as a reference electrode, and stainless steel is used as a counter electrode, the temperature of the electrolyte is set to 30°C, the scanning range is set to ±0.3VvsPt electrode, and the scanning speed is 500mV / sec, the voltage is linearly scanned, and the maximum value of the current value of the cyclic voltammogram measured when the electrode material of one embodiment of the present invention is used as the working electrode is compared with the maximum value of the current value measured when the smooth substrate is used as the working electrode, and it is set as an index about the electrochemical effective surface area. Then, the maximum value of the current value when the electrode material of one embodiment of the present invention is used as the working electrode is preferably set to 6.5 times or more of the maximum value of the current value when the smooth substrate is used as the working electrode. By configuring the electrode material to be 6.5 times or more when the smooth substrate is used as the working electrode, the ESR reduction effect brought about by the improvement of the retention force of the solid electrolyte and the electrolyte can be obtained.

[0150] Regarding the evaluation method of the bonding between the atoms of the metal element constituting the first conductive layer and the carbon atoms, XPS can be used to analyze the presence and bonding state of each element in the depth direction. By repeating etching and measurement every several nm, it is possible to analyze: the ratio of the presence of the bonding between the atoms of the metal element constituting the first conductive layer and the carbon atoms relative to the total presence of all the bondings in which the detected carbon atoms participate. Therefore, when the ratio is 5% or more, a low-resistance conductor can be obtained to obtain an ESR reduction effect, so the ratio of the presence of the bonding between the atoms of the metal element constituting the first conductive layer and the carbon atoms relative to the total presence of all the bondings in which the detected carbon atoms participate is preferably 5% or more.

[0151] In addition, when the electrode material of one embodiment of the present invention using a valve metal as the substrate 2 is used as the cathode foil of the electrolytic capacitor, when a current that converges within the current density range of the leakage current of the electrolytic capacitor due to electrochemical polarization flows, the potential corresponding to the current can be located on the higher potential side compared to the natural immersion potential of the control cathode foil of the same type and purity of 99.99% or more as the valve metal used in the substrate 2, and the natural immersion potential when immersed in the electrolyte can also be located on the higher potential side compared to the natural immersion potential of the control cathode foil of the same type and purity of 99.99% or more as the valve metal used in the substrate 2 when immersed in the same electrolyte (Patent Documents 26, 27). Accordingly, when the dielectric oxide film formed on the anode foil is repaired by the leakage current, the generation of hydrogen gas on the cathode side can be suppressed. To further illustrate this point, a natural oxide film is formed on the above-mentioned control cathode foil, and has a natural immersion potential that causes the cathode reaction of reducing hydrogen ions to occur predominantly. In addition, the cathode foil of one embodiment of the present invention has a natural immersion potential that is on the higher potential side compared to the above-mentioned control cathode foil. Therefore, even when the cathode foil of one embodiment of the present invention is assembled in an electrolytic capacitor and a leakage current is generated, the potential of the cathode foil of one embodiment of the present invention can be maintained on the higher potential side compared to the natural immersion potential of the above-mentioned control cathode foil. Therefore, the potential of the cathode foil of one embodiment of the present invention when a leakage current is generated in the electrolytic capacitor is within the range of potentials that make the cathode reaction of reducing dissolved oxygen dominantly generated, while suppressing the cathode reaction of reducing hydrogen ions. As a result, the internal pressure rise of the electrolytic capacitor caused by the generation of hydrogen gas is suppressed, and the risk of expansion of the housing that accommodates the capacitor element can be reduced.

[0152] As described above, the method for obtaining the actual surface area required for the inorganic conductive layer having a concave-convex portion on the surface side of the first conductive layer and the second conductive layer to hold the solid electrolyte and the electrolyte can be cited as the BET specific surface area method of adsorbing nitrogen or krypton. When krypton gas with a saturated vapor pressure lower than that of nitrogen is used as the adsorbed gas, high-precision measurements can be performed even in areas with a small specific surface area. It is preferred that the surface expansion ratio (BET specific surface area of ​​the electrode material / BET specific surface area of ​​the smooth substrate) calculated from the BET specific surface area using krypton gas as the adsorbed gas is set to 1.5 or more. By setting this surface expansion ratio to 1.5 times or more, the retention of the solid electrolyte and the electrolyte can be further improved to obtain a further ESR reduction effect. However, although the first conductive layer can be further thickened to further increase the surface area, when it is too thick, the volume efficiency of the capacitor will decrease, and the manufacturing cost will also increase. Therefore, it is particularly preferred that the surface expansion ratio calculated from the BET specific surface area using krypton gas as the adsorbed gas is set to 1.5 times or more and 200 times or less.

[0153] Fig.30 Parts a) to d) of are scanning electron microscope (SEM) surface photographs of the cathode foils of Examples 2, 4, 5 and 6. Here, particles are photographed in the SEM photographs, which are the surface side of the electrode material, that is, the convex part of the concave and convex part of the surface side of the inorganic conductive layer. As described above, the electrode material 1 is sequentially formed with an oxide layer 3, a first conductive layer 4, a mixed layer 7 and a second conductive layer 5 on a smooth substrate 2, and has a concave and convex part on the surface side of the first conductive layer 4. Then in Examples 2, 4, 5 and 6, the first conductive layer is a particle deposition layer formed by evaporation, and a mixed layer and a second conductive layer are formed thereon, and the thickness of the mixed layer and the second conductive layer are both thin. In this way, when the surface of the cathode foil of each example is observed by SEM, as shown Fig.30 As shown in parts a) to d) of , it seems that a sample in which only a first conductive layer like a particle deposition layer is formed has been observed. That is, each particle confirmed in the surface photograph of the SEM corresponds to an individual convex portion of the inorganic conductive layer. Therefore, in Examples 2, 4, 5 and 6, the particle size of the particles confirmed in the surface photograph of the SEM is set to the diameter of the convex portion of the concave-convex portion on the surface side of the inorganic conductive layer. Specifically, a JSM-7401F manufactured by NEC Corporation is used as a scanning electron microscope to observe the surface of the cathode foil of each example at an observation magnification of 100,000 times, and then the Feret diameter of the particles present in the observation field at this time is measured, and the Feret diameter is set to the diameter of the convex portion. In addition, the so-called Feret diameter here is Fig.30 As shown in part a), it means the distance between the tangent on the left side and the tangent on the right side of the particle parallel to the longitudinal direction of the field of view in the tangent relative to the particle. When the diameter of this convex portion is too large, the surface area of ​​the concave and convex portion on the surface side of the surface layer in the electrode material becomes smaller, and the geometric structure required to maintain the solid electrolyte and the electrolyte cannot be obtained. Therefore, it is preferred to set the average diameter of the convex portion of the concave and convex portion on the surface side of the inorganic conductive layer to be less than 210nm. In addition, the so-called average diameter here means the average value of the Feret diameter measured for 50 particles (convex portions) present in the observation field of view. However, when the number of particles in only one field of view is less than 50, other fields of view can be further measured until the number of particles reaches 50.

[0154] Electrolytic capacitor of the present invention

[0155] The following describes a solid electrolytic capacitor and a hybrid capacitor as examples of electrolytic capacitors that can be produced using the cathode foil of the present invention. Figures 1 to 4 Although the present invention is not limited to the case of cathode foil 1 having a layer structure of , the electrolytic capacitor of the present invention can be manufactured even when cathode foil 1 having a layer structure in which each layer is stacked on one side of substrate 2 is used.

[0156] (Solid Electrolytic Capacitors)

[0157] Fig. 9 For use with the above Figures 1 to 4 The exploded view of the wound solid electrolytic capacitor 8 made of the cathode foil 1 of any layer structure shown. The solid electrolytic capacitor 8 can be made by the following method:

[0158] (i) The anode foil 9 is formed by anodizing an aluminum foil to form an oxide film, and the Figures 1 to 4 Cathode foil 10 of any of the layer structures shown is stacked with separator 11 interposed therebetween, and after anode terminal 13 is connected to anode foil 9 and cathode terminal 14 is connected to cathode foil 10 , the whole is wound to produce capacitor element 12 .

[0159] (ii) After the capacitor element 12 is immersed in a mixed solution of 3,4-ethylenedioxythiophene containing n-butanol as a diluent and iron (II) p-toluenesulfonate as an oxidant, it is heated to form a solid electrolyte layer of polyethylene dioxythiophene (PEDOT) by thermal polymerization. Alternatively, in order to disperse polyethylene dioxythiophene in an aqueous solution, it can be immersed in a PEDOT / PSS aqueous dispersion solution mixed with polystyrene sulfonic acid (PSS), and dried after impregnation to form a solid electrolyte layer.

[0160] (iii) The capacitor element 12 on which the solid electrolyte layer is formed is housed in the aluminum case 15 and sealed with the sealing rubber 16 .

[0161] In addition, a solid electrolyte layer can also be formed by conductive polymers such as polypyrrole, polyaniline, polyacene, polyparaphenylene vinylene, polyisothianaphthene, or by manganese dioxide (MnO2) or TCNQ (TetracyanoQuinodimethane) complex salts.

[0162] (Hybrid Capacitor)

[0163] The hybrid capacitor is made in the same manner as the solid electrolytic capacitor 8, and after performing steps (i) and (ii), is made by the following method:

[0164] (ii-2) The capacitor element having the solid electrolyte layer formed thereon is impregnated with an electrolyte solution containing at least one of γ-butyrolactone, ethylene glycol, and water as a solvent.

[0165] (iii) The capacitor element having the solid electrolyte layer formed thereon and impregnated with the electrolyte solution is housed in an aluminum case and sealed with a sealing rubber.

[0166] In addition, the solid electrolyte layer can also be formed by conductive polymers such as polypyrrole, polyaniline, polyphenylene, polyisothianaphthene, or manganese dioxide (MnO2) or TCNQ (tetracyanoquinodimethane) complex salts.

[0167] [Example]

[0168] The following describes the structures, analysis results, performance test results, etc. of various cathode foils and electrolytic capacitors produced as examples of the present invention.

[0169] Fig.10 This is a TEM (transmission electron microscope) photograph (cross-sectional image) of a cathode foil (Example 2 described later) using an electrode material according to one embodiment of the present invention. Fig.10 The cathode foil has Figure 8 The layer structure shown ( Figure 4 The layer structure on one side shown in the figure) (it can be considered that a natural oxide film is formed between the smooth substrate and the dense layer), and on the aluminum smooth substrate 2 (with the natural oxide film 3 formed), a dense layer 6 of Ti is formed by arc ion plating, and a first conductive layer 4 of Ti is formed by vacuum evaporation, and then a carbon layer (second conductive layer 5) of GLC is formed by arc ion plating. This cathode foil has the following advantages:

[0170] By using a smooth substrate as the substrate 2, the Al surface can be covered with Ti without gaps.

[0171] .By forming a granular deposition structure, the polymer or electrolyte can be closely adhered and retained.

[0172] .Ti pretreatment by arc ion plating can eliminate the influence of residual oil or oxide on the surface of the substrate.

[0173] also, Fig.11 To display and Fig.10 The TEM photograph (cross-sectional image) of another cathode foil (Example 4 described later) which is different from the cathode foil shown. Fig.10 , Fig.11 The cathode foils shown are all made by forming a dense layer 6 of Ti by arc ion plating on an aluminum smooth substrate 2 (with a natural oxide film 3 formed thereon), forming a first conductive layer 4 of Ti by vacuum evaporation, and then forming a carbon layer (second conductive layer 5) of GLC by arc ion plating. However, the metal material contained in the first conductive layer 4 (on the Fig.10 , Fig.11 The particle size of Ti) in the sample is different, so the fineness of the concavities and convexities in the first conductive layer 4 is different.

[0174] Fig.12 For Fig.10 STEM (scanning transmission electron microscope) photograph (cross-sectional image) of the same cathode foil (Example 2), Fig.13 For Fig.11 STEM photo (cross-sectional image) of the same cathode foil (Example 4). As described above, in the first conductive layer 4, the particle size of the metal material can be appropriately controlled by adjusting conditions such as the type of introduced gas or the degree of vacuum, the temperature of the substrate, etc. during evaporation, so the first conductive layer 4 can be formed with various particle sizes, that is, various degrees of concavity and convexity.

[0175] Fig.14 For Fig.10 TEM images (bright field image, cross-sectional image) of the same cathode foil (Example 2), Fig.15 For Fig.11 TEM images (bright field image, cross-sectional image) of the same cathode foil (Example 4) In both samples of Example 2 and Example 4, a natural oxide film (about several nanometers) on the substrate can be identified.

[0176] Fig.16 To display and Fig.10 A graph showing the analysis results of the same cathode foil (Example 2) measured by ToF-SIMS (time-of-flight secondary ion mass spectrometry) (showing the cross-sectional distribution of the chemical bonding state), Fig.17 To display and Fig.11 A graph showing the analysis results of the same cathode foil (Example 4) measured by ToF-SIMS (showing the cross-sectional distribution of the chemical bonding state). Fig.16 , Fig.17 In the graph, the vertical axis represents the secondary ion intensity (Intensity), and its unit is [counts] which represents the number of each secondary ion detected at each measurement depth point. Fig.16 , Fig.17 In the chart, carbon C6 from carbon evaporation is a univalent negative ion of fragment (block) ions composed of 6 C atoms, metal titanium Ti2 ions are univalent negative ions composed of 2 Ti atoms, metal aluminum (underlying metal) Al5 ions are univalent negative ions composed of 5 Al atoms, and the other TiC2 / TiO2 / TiN / TiNO / Al2O3 are negative ions in molecular bonding states. For example, Fig.17In Example 4 shown, it can be seen that the presence of metal Ti is only a little at the interface of the substrate, and most of it exists in the form of carbide / oxide / nitride / nitride oxide. In addition, in both samples of Example 2 and Example 4, it can be seen that a mixed layer of oxide and Ti compound and a mixed layer of Ti compound and C are formed on the aluminum substrate, respectively, and a mixed layer is formed as a gradient coating in which the ratio of C increases toward the outermost layer (carbon layer).

[0177] Fig.18 For Fig.10 , Fig.11 The sample shown is a graph of the Raman scattering spectrum (full wave number region) of the cathode foil as a sample produced under the same conditions and measured by laser micro-Raman spectroscopy. Fig.19 For Fig.10 , Fig.11 The sample shown is a graph of the Raman scattering spectrum (CC bond region) of the cathode foil as a sample produced under the same conditions and measured by laser micro-Raman spectroscopy. Fig.18 In the graph, the Raman shift on the horizontal axis is 1500 cm -1 The graph with a larger Raman intensity [counts] on the vertical axis corresponds to the sample of Example 2, and the Raman shift on the horizontal axis is 1500 cm -1 The graph with a smaller Raman intensity [counts] on the vertical axis corresponds to the sample of Example 4. Fig.19 In the graph, the Raman shift on the horizontal axis is 1100 cm -1 The graph with a smaller Raman intensity [counts] on the vertical axis corresponds to the sample of Example 2, and the Raman shift on the horizontal axis is 1100 cm -1 The graph with a larger Raman intensity [counts] on the vertical axis corresponds to the sample of Example 4. Fig.19 From the graph shown, it can be seen that in the two samples of Example 2 and Example 4, sp 2 The Raman intensity in the (G band) is relatively high compared to the sp 3 Since the Raman intensity in (D band) is high, it can be seen that the carbon layer (second conductive layer) in both samples is formed by containing GLC.

[0178] Fig.33 For Fig.10 , Fig.11 The sample shown is a cathode foil produced under the same conditions. The spectrum was measured by XPS after scanning the 280-290 eV range in a narrow range at a location after etching 36 nm from the surface. When the peak due to the C bonding state observed near 280-290 eV was separated, the peak due to the sp bonding state appeared at around 284.5 eV.2 The peak at 285.5 eV is due to the sp 3 Therefore, it can be known that the carbon layer in the two samples of Example 2 and Example 4 is an amorphous structure (amorphous structure) having both graphite and diamond bonds. In addition, when comparing the peak areas, it can be known that sp 2 The peak area is larger than sp 3 Therefore, it can be known not only from the laser micro-Raman spectroscopy but also from XPS that the carbon layers in the two samples are formed of graphite-like carbon containing a graphite bonding ratio exceeding 50%.

[0179] Fig.32 Part a) shows the Fig.10 The samples shown are samples made under the same conditions, and the graph shows the atomic ratio in the depth direction measured by XPS. By repeatedly etching and measuring in units of several nm from the surface, the Fig.32 The amount of presence in the depth direction of part a). Fig.32 Part b) shows the Fig.10 The samples shown were Fig.33 The peaks generally caused by the C bonding state are separated until no C is detected, and then the horizontal axis is set to the SiO2 conversion depth, and the vertical axis is set to the total of all C bonding states and the TiC bonding graph when the peak area of ​​each C bonding state is set (in addition, at Fig.32 In the sample to be analyzed, since the metal element constituting the first conductive layer is titanium, "TiC bonding" is equivalent to "bonding of atoms of the metal element constituting the first conductive layer and carbon atoms"). The integral value is calculated for each curve, and the value obtained by dividing the amount of TiC bonding state (near 282eV) by the amount of all C bonding states is set as the abundance ratio of TiC bonding. In the case of other metal carbides, it can be calculated from peaks such as Al4C3 bonding state (near 282.4eV), TaC bonding state (near 281.9eV), NbC bonding state (near 281.9eV), VC bonding state (near 282.5eV), and WC bonding state (near 283.0eV).

[0180] Performance test of the hybrid capacitor of the present invention

[0181] Cathode foils of Examples 1 to 11 were prepared as cathode foils of one embodiment of the present invention, and cathode foils of Comparative Examples 1 to 3 were prepared as cathode foils of Comparative Examples. Hybrid capacitors of Examples 1 to 11 were manufactured using the cathode foils of Examples 1 to 11, and hybrid capacitors of Comparative Examples 1 to 3 were manufactured using the cathode foils of Comparative Examples 1 to 3, respectively. Performance tests (ESR measurements) were performed on each of the manufactured hybrid capacitors. The manufacturing conditions and ESR measurement conditions of each hybrid capacitor are described below.

[0182] Example 1: Ar gas is introduced into a processing chamber container which is evacuated to 0.003 Pa, and in the process of placing the first and second targets adjacent to each other in the order of a first target made of Ti material and a second target made of graphite material, in a manner that the vapors or ions of the deposition materials radiated from the first and second targets toward the substrate in a conical shape intermingle with each other (contact manner) before reaching the substrate, a smooth foil of aluminum is sequentially conveyed, and a 200 nm Ti layer having irregularities is provided by electron beam evaporation, and then a carbon film is formed by arc ion plating. By continuous film formation in this roll-to-roll manner, mixed layers are obtained at the interface between the oxide layer and the first conductive layer on the smooth substrate and at the interface between the first conductive layer and the second conductive layer (in addition, the mixed layer formed at the interface between the oxide layer and the first conductive layer is a layer in which a substance constituting the oxide layer and a substance constituting the first conductive layer are mixed, which is different from a layer in which a substance constituting the first conductive layer and a substance constituting the second conductive layer are mixed). The foil is used as the cathode and combined with the anode foil (etched aluminum foil after anodization at 53V) to make a hybrid capacitor, and then the initial ESR (100kHz) is measured, and then the ESR (100kHz) is measured again after being placed at 125°C for 2000hr (1hr is 60 minutes). In addition, the hybrid capacitor is made in the following manner. That is, first, the anode foil and the cathode foil made as described above are overlapped with a separator paper, and after the anode terminal is connected to the anode foil and the cathode terminal is connected to the cathode foil, this is wound to make a capacitor element. Then, in a container that is vacuum-drawn to about 7000Pa, the capacitor element is immersed in a polymer dispersion solution of an aqueous solvent, and then dried at 150°C for 30 minutes in an atmospheric environment to form a solid electrolyte layer. Then, in a container that is vacuum-drawn to about 5000Pa, an electrolyte containing ethylene glycol as a solvent is impregnated into the capacitor element. Then, finally, the capacitor element is housed in an aluminum casing and sealed with a sealing rubber.

[0183] Example 2: The same amount of Ar gas as in Example 1 was introduced into the processing chamber container which was evacuated to 0.003 Pa, and then a smooth aluminum foil was transported and a Ti film of 10 nm was formed by arc ion plating. Then, as in Example 1, the aluminum foil on which the Ti layer was formed by arc ion plating was transported to the film forming process, and a 200 nm Ti layer with unevenness was provided by evaporation, and then a carbon film was formed by arc ion plating. The rest was the same as in Example 1.

[0184] Example 3: A smooth substrate that has been anodized in a diammonium phosphate solution at an applied voltage of 5 V is used. Other treatments are the same as those in Example 2.

[0185] Example 4: Except that the introduced gases are Ar and N2, everything else is the same as Example 2.

[0186] Example 5: The same as Example 2 except that the thickness of the Ti layer having irregularities provided by vapor deposition was set to 70 nm.

[0187] Example 6: The process is the same as that of Example 2 except that an Al film is formed by arc ion plating to replace Ti, and then an Al layer having irregularities is provided by evaporation to replace the Ti layer having irregularities.

[0188] Example 7: Except that the amount of Ar gas introduced is 1 / 40 of that in Example 2, other conditions are the same as those in Example 2.

[0189] Example 8: Except that the amount of Ar gas introduced is one tenth of that in Example 6, other conditions are the same as those in Example 6.

[0190] Example 9: The same as Example 2 except that the thickness of the Ti layer having irregularities provided by vapor deposition was set to 30 nm.

[0191] Example 10: The same as Example 1 except that an Al layer is provided by evaporation instead of the Ti layer having irregularities.

[0192] Example 11: Except that the introduced gas is only N2 gas, everything else is the same as Example 2.

[0193] Comparative Example 1: A smooth substrate was used and the same amount of Ar gas as in Examples 1 to 3 was introduced, Ti was formed by arc ion plating, and then carbon was formed by arc ion plating, which was then used as a cathode. Other conditions were the same as in Example 1.

[0194] Comparative Example 2: Using an etched foil after anodizing the substrate at 2 V, the same amount of Ar gas as in Examples 1 to 3 was introduced, Ti was formed by arc ion plating, and then carbon was formed by arc ion plating, and then used as a cathode. Other conditions were the same as in Example 1.

[0195] Comparative Example 3: A (dense) Ti layer was formed by vacuum deposition without introducing gas into a smooth substrate, and then N2 gas was introduced until the pressure in the container became the same as that in Examples 1 to 3, and a (concave and convex) Ti layer was formed by vacuum deposition, and this was used as a cathode. Other conditions were the same as those in Example 1. In addition, the coating structure of the cathode foil of Comparative Example 3 was the same as the coating structure disclosed in the specification of Japanese Patent Application Laid-Open No. 2014-022707.

[0196] In the cathode foils of Examples 1 to 11 and Comparative Examples 1 and 2 in which the carbon conductive layer is formed, a mixed layer is formed below the carbon conductive layer. In the mixed layer, carbon and a material constituting a layer below the mixed layer exist in a mixed state. In addition, the carbon layer in Examples 1 to 11 and Comparative Examples 1 and 2 contains GLC.

[0197] In the cathode foil of the embodiment and comparative example, the current value flowing is measured by cyclic voltammetry. The measurement is carried out in a glove box and in a nitrogen environment. 1M tetraethylammonium hexafluorophosphate with propylene carbonate as a solvent is prepared as a measuring solution. The measurement is configured as a three-electrode type, with the relative electrode being stainless steel, the reference electrode being a Pt electrode, and the working electrode being the cathode foil of each embodiment or comparative example. The measurement conditions of the cyclic voltammetry are set to a measuring solution temperature of 30°C, a scanning range of ±0.3V, and a scanning speed of 500mV / sec. The current and voltage are recorded from 1 to 5 cycles and the maximum value of the current of each cycle is calculated, and the average value of these is set as the maximum current value of the cathode foil of the embodiment or comparative example. Similarly, the maximum current value is measured for the smooth substrate monomer, and the maximum current value of the cathode foil of each embodiment and comparative example is represented by the maximum current value of 1.

[0198] For the cathode foils of the examples and comparative examples, etching and measurement were repeated in units of 2.5 nm in terms of SiO2 by XPS to confirm the bonding state in the depth direction. The XPS apparatus used was JPS-9010TR manufactured by JEOL Ltd. and the measurement was performed under the following conditions.

[0199] .X-ray source: AlKα, tube voltage: 10kV, tube current: 10mA, microscopic analysis: none, dwell: 100msec, planar emission tube: 3.0V 4.0mA

[0200] .Step: Wide range 1.0eV / Narrow range 0.05eV

[0201] .Pass: Wide range 50eV / Narrow range 20eV

[0202] .Scans: Wide range 1 / Narrow range 2

[0203] The peaks of the C bonding states observed from 270 eV to 290 eV measured in the measurement range of 0.05 eV were separated, and the peak area of ​​each C bonding state was calculated. The integral value of the curve drawn when the horizontal axis was set as the SiO2 conversion depth and the vertical axis was set as the peak area of ​​each C bonding state was calculated, and this was set as the abundance of each C bonding state. The value obtained by dividing the abundance of all C bonding states by the abundance of TiC bonding states (near 282 eV) or Al4C3 bonding states (near 282.4 eV) was set as the abundance ratio of the bonding of the metal element atoms to the carbon atoms in the cathode foil of each embodiment and comparative example.

[0204] For the cathode foils of the examples and comparative examples, the sp peaks obtained by separating the peaks due to CC bonding measured by Raman spectroscopy were measured. 2 The half-width of the peak of the band (G band). As an example, Fig.35 for Fig.10 The samples shown are derived from the spectrum of CC bonding obtained by Raman spectroscopy, which was peak separated and the half-width of the G band peak was measured. The measurement was performed using an inVia Qontor manufactured by Renishaw, irradiated with a laser of a wavelength of 532 nm and used a range of 100 to 3200 cm -1 The half-peak width of crystalline graphite was measured in the same manner, and this was taken as 1 to be the magnification of the half-peak width of each Example and Comparative Example.

[0205] Fig. 20 TABLE 1 is a table showing the results of ESR measurement of the hybrid capacitors of Examples 1 to 11 and Comparative Examples 1 to 3. Fig. 20 The term "after 2000 hours of degradation" means that the hybrid capacitor is subjected to 2000 hours of degradation in an atmosphere of 125°C and then the ESR is measured. Fig. 20From the ESR measurement results, it can be seen that first, in the initial state, the ESR of the hybrid capacitors of Examples 1 to 3, 6 and 7 is lower than the ESR of the hybrid capacitors of Comparative Examples 1 to 3, and the ESR of the hybrid capacitors of Examples 4, 5 and 8 to 11 is lower than the ESR of the hybrid capacitors of Comparative Examples 1 and 3 (in addition, the ESR is almost the same as the ESR of the hybrid capacitor of Comparative Example 2). After 2000 hr degradation, the ESR of the hybrid capacitors of Examples 1 to 11 is lower than the ESR of the hybrid capacitors of Comparative Examples 1 to 3. That is, by using an electrode material having an oxide layer, a first conductive layer containing a metal, a mixed layer in which a substance constituting the first conductive layer and a substance constituting the second conductive layer are mixed, and a second conductive layer containing carbon, and having a concave-convex portion on the surface side of the first conductive layer, as a cathode foil, the ESR of the hybrid capacitor in the initial stage and after 2000 hr degradation can be reduced. In addition, Comparative Example 1 is the same as Examples 1 to 11 in that an oxide layer, a first conductive layer containing a metal, a mixed layer formed by a mixture of a substance constituting the first conductive layer and a substance constituting the second conductive layer, and a second conductive layer containing carbon are sequentially formed on a smooth substrate, but the difference from Examples 1 to 11 is that there is no concave-convex portion on the surface side of the first conductive layer. Therefore, it does not have a geometric structure suitable for retaining a solid electrolyte and an electrolyte, and both the initial ESR and the ESR after 2000hr degradation are high. Comparative Example 2 is the same as Examples 1 to 11 in that an oxide layer, a first conductive layer containing a metal, a mixed layer formed by a mixture of a substance constituting the first conductive layer and a substance constituting the second conductive layer, and a second conductive layer containing carbon are sequentially formed on a substrate, but the difference from Examples 1 to 11 is that an etching substrate is used as a substrate instead of a smooth substrate. Therefore, during film formation, the entire surface of the substrate (especially the inner wall of the etching pit) cannot be covered, and a portion is exposed, and the ESR after 2000hr degradation increases. Comparative Example 3 is the same as Examples 1 to 11 in that an oxide layer and a first conductive layer containing a metal are sequentially formed on a smooth substrate, and that the surface side of the first conductive layer has a concave-convex portion. However, unlike Examples 1 to 11, a mixed layer in which a substance constituting the first conductive layer and a substance constituting the second conductive layer are mixed and a second conductive layer containing carbon is not further formed on the first conductive layer. Therefore, the first conductive layer is in direct contact with the solid electrolyte, increasing the interface resistance, and both the initial ESR and the ESR after 2000 hr degradation become higher.

[0206] also, Fig. 20The cathode foils of Examples 1 to 11 and Comparative Examples 1 to 3 are also shown with respect to the measurement results obtained by cyclic voltammetry, the measurement results obtained by XPS, and the measurement results obtained by Raman spectroscopy. In Examples 1 to 11, the ESR of the hybrid capacitor of Example 9 is almost the same as that of the hybrid capacitors of Examples 1 to 8, 10, and 11 at the initial stage, but after 2000 hours of degradation, the ESR of the hybrid capacitor of Example 9 is higher than that of the hybrid capacitors of Examples 1 to 8, 10, and 11. In this regard, the maximum current value multiplier obtained by cyclic voltammetry is 6.5 times or more in the cathode foils of Examples 1 to 8, 10, and 11, whereas it is only 6.0 times in the cathode foil of Example 9. Therefore, in Example 9, compared with other examples, the effective electrochemical surface area after considering the ease of electricity flow is insufficient, and the ESR reduction effect brought about by the improved retention of the solid electrolyte and the electrolyte cannot be fully exerted, so that the ESR after 2000hr degradation increases. Therefore, the maximum current value measured by cyclic voltammetry is preferably 6.5 times or more.

[0207] Regarding Examples 1 to 8, 10 and 11, the ESR of the hybrid capacitor of Example 10 was almost the same as that of the hybrid capacitor of Examples 1 to 8 and 11 at the initial stage, but after 2000 hours of degradation, the ESR of the hybrid capacitor of Example 10 was higher than that of the hybrid capacitor of Examples 1 to 8 and 11. In this regard, the ratio of metal carbides measured by XPS was 5% or more in the cathode foil of Examples 1 to 8 and 11, while it was only 3% in the cathode foil of Example 10. Therefore, in Example 10, compared with other Examples, the increase in interface resistance caused by the rapid change in the composition of the electrode material between the first conductive layer containing metal and the second conductive layer containing carbon could not be suppressed, and a sufficiently low-resistance conductor was not formed, so the ESR after 2000 hours of degradation increased. In addition, the metal carbides detected by XPS also include those present in the mixed layer. Therefore, in addition to the maximum current value magnification measured by cyclic voltammetry being 6.5 times or more, it is particularly preferred that a mixed layer is formed between the first conductive layer and the second conductive layer and the ratio of metal carbide measured by XPS is 5% or more.

[0208] Regarding Examples 1 to 8 and 11, the ESR of the hybrid capacitor of Example 11 was almost the same as that of the hybrid capacitor of Examples 1 to 8 at the initial stage, but after 2000 hours of degradation, the ESR of the hybrid capacitor of Example 11 was higher than that of the hybrid capacitor of Examples 1 to 8. In this regard, the half-width of the G band peak measured by Raman spectroscopy was 3.8 times or more in the cathode foil of Examples 1 to 8, while it was only 3.5 times in the cathode foil of Example 11. Therefore, in Example 11, the amorphous degree of carbon was low and the degradation resistance was poor compared with other Examples, and the ESR after 2000 hours of degradation increased. Therefore, in addition to the maximum current value measured by cyclic voltammetry being multiplied by 6.5 times or more, a mixed layer is formed between the first conductive layer and the second conductive layer, and the ratio of metal carbide measured by XPS is more than 5%, and the half-width of the G band peak measured by Raman spectroscopy is more preferably multiplied by 3.8 times or more.

[0209] Fig.36 The figure shows the ratio of the BET specific surface area measured by the Kr adsorption method relative to the smooth substrate (surface expansion ratio) and the ESR after 2000 hr degradation of the cathode foils of Examples 1 to 8. Examples 1 to 6 and 8, in which the surface expansion ratio measured by the Kr adsorption method is 1.5 times or more, have lower ESR after 2000 hr degradation than Example 7, in which the surface expansion ratio measured by the Kr adsorption method is 1.4 times. Therefore, in addition to the ratio of the maximum current value measured by cyclic voltammetry being 6.5 times or more, a mixed layer being formed between the first conductive layer and the second conductive layer, the ratio of the metal carbide measured by XPS being 5% or more, and the ratio of the half-peak width of the G band peak measured by Raman spectroscopy being 3.8 times or more, the surface expansion ratio measured by the Kr adsorption method is particularly preferably 1.5 times or more.

[0210] Fig.31 The average diameter of the convex part of the concave-convex part on the surface side of the inorganic conductive layer after the carbon conductive layer is applied in the cathode foil of Examples 1 to 6 and 8, and the ESR after 2000 hr degradation. The ESR after 2000 hr degradation is lower in Examples 1 to 6 with an average diameter of 210 nm or less than that in Example 8 with an average diameter of 230 nm. Therefore, in addition to the maximum current value measured by cyclic voltammetry having a magnification of 6.5 times or more, a mixed layer is formed between the first conductive layer and the second conductive layer, the ratio of metal carbide measured by XPS is 5% or more, and the magnification of the half-peak width of the G band peak measured by Raman spectroscopy is 3.8 times or more, and the surface expansion magnification measured by Kr adsorption method is 1.5 times or more, the average diameter of the convex part of the concave-convex part on the surface side of the inorganic conductive layer is particularly preferably 210 nm or less.

[0211] The following is about the ultrathin section samples in the thickness direction of the entire coating portion including the base material portion close to the coating. Fig. 22 For Fig.10 The cross-sectional distribution of elements of the same cathode foil (Example 2) measured by TEM-EDS (transmission electron microscopy-energy dispersive X-ray analysis) is as follows: Fig.23 For Fig.11 The cross-sectional distribution of elements of the same cathode foil (Example 4) measured by TEM-EDS. Fig.24 For Fig.10 The cross-sectional distribution of elements (relatively) of the same cathode foil (Example 2) measured by STEM-EELS (Scanning Transmission Electron Microscopy-Electron Energy Loss Spectroscopy) Fig.25 is located on the carbon conductive layer side), Fig.25 For Fig.10 The cross-sectional distribution of elements measured by STEM-EELS of the same cathode foil (Example 2) ( Fig.24 is located on the substrate side). Fig.26 For Fig.11 The cross-sectional distribution of elements measured by STEM-EELS of the same cathode foil (Example 4) ( Fig. 27 is located on the carbon conductive layer side), Fig. 27 For Fig.11 The cross-sectional distribution of elements measured by STEM-EELS of the same cathode foil (Example 4) ( Fig.26 Here, Figure 22 to Figure 27 In the equation, K represents the K shell of the electron shell. Figure 24 to Figure 27 In , L represents an L shell of an electron shell. In both Examples 2 and 4, it was found that a mixed layer existed below the carbon conductive layer.

[0212] Performance test of the solid electrolytic capacitor of the present invention

[0213] In addition, the cathode foils of the above-mentioned Examples 1 to 11 and Comparative Examples 1 to 3 were used to respectively manufacture solid electrolytic capacitors of Examples 1 to 11 and Comparative Examples 1 to 3 (they were manufactured by a manufacturing method that differed from the manufacturing method of the hybrid capacitors of Examples 1 to 11 and Comparative Examples 1 to 3 only in that the capacitor element was not impregnated with an electrolyte after forming a solid electrolyte layer), and performance tests (ESR measurements) were performed on each of the manufactured solid electrolytic capacitors.

[0214] Fig.21The table shows the results of ESR measurement of the solid electrolytic capacitors of Examples 1 to 11 and Comparative Examples 1 to 3. In the initial state, the ESR of the solid electrolytic capacitors of Examples 1 to 11 is lower than that of the solid electrolytic capacitors of Comparative Examples 1 and 3.

[0215] Evaluation of physical properties of the electrode material of the present invention

[0216] The bonding mechanism between the solid electrolyte and the cathode foil is of adhesive tape type. Fig.28 Comparative data of the bonding degree using industrial adhesive tape. The adhesive tape is a 10mm wide polypropylene adhesive tape made by Nitto Denko Co., Ltd., which is cut into 15cm long with the bonding surface facing down, and then gently placed on a test piece cut into 50mm wide × 200mm long in parallel to the length direction, and a pressing roller with a load of 20N is moved back and forth once on the tape at a length of more than 100mm, and bonding is performed with a uniform load. One end of the sample piece is firmly pressed by a clamp, and the tape on the opposite side of the side bonded to the sample piece is folded back 180° near the clamp, and the end is fixed by a clamp connected to a push-pull gauge, and pulled at a constant speed of 10mm / second. The average value of the tensile load (gf / cm) when the tape is peeled off is read and set as the tape bonding degree. Regarding Examples 1, 2, 4, and 5, the anchoring bonding effect brought about by the concavo-convex structure imparted to the surface layer side is reflected, and a very strong tape bonding degree is obtained compared to Comparative Example 1 in which the concavo-convex structure is not imparted to the surface layer side. In other words, it can be seen that by imparting the concavo-convex structure to the surface layer side of the first conductive layer, an effect of improving the adhesion with the solid electrolyte can be obtained.

[0217] In recent years, hybrid capacitors have been used to disperse polyethylene dioxythiophene (PEDOT) in an aqueous solution, and the solid electrolyte layer is formed by dipping and impregnating the PEDOT / PSS aqueous dispersion mixed with polystyrene sulfonic acid (PSS) from the viewpoints of heat resistance, conductivity, withstand voltage, and manufacturing cost. The adhesion or retention of the solid electrolyte is also considered to be dependent on the wettability or surface free energy of the cathode foil. Fig.29 are the contact angles (°) with respect to water, a highly polar solvent, and diiodomethane (CH2I2), a less polar solvent, and the surface free energy (mJ / m 2)'s connotation (polar hydrogen bonding component and non-polar dispersing power component). The polar hydrogen bonding component is related to the affinity with the water solvent, and the non-polar dispersing power component is related to the affinity with hydrocarbons or organic solvents, polymers, etc. 1 μL of droplets of each solvent of water and diiodomethane is dropped on a horizontally stationary sample piece, and the contact angle of the droplet is measured after 60 seconds using a contact angle meter (DM-501Hi) manufactured by Kyowa Interface Science Co., Ltd. With regard to Examples 2 and 4, due to the concave-convex structure imparted to the surface side, compared to Comparative Example 1 in which the concave-convex structure is not imparted to the surface side, extremely low contact angles (excellent wettability) relative to the two solvents and high surface free energy values ​​with good balance relative to the two components are obtained.

[0218] When the capacitor element is a roll-type element made by winding between long strips of electrode foil on the anode side and the cathode side with separator paper interposed therebetween, there is a concern that the element may cause winding deviation when the cathode foil is clamped by a reel and winding begins. This is because when the coefficient of friction between the separator paper in contact with the cathode foil near the reel is small, when the reel is pulled out after the roll-type element is formed, the clamping force (friction force) between the cathode foil and the separator paper is insufficient, causing the cathode foil in contact with the reel to move in the direction of pulling out the reel.

[0219] Fig.34 The data are compared with the coefficient of friction of separator paper. The separator paper used was a 40 μm thick separator paper (RTZ3040) made of natural cellulose made by Nippon Kodoshi Co., Ltd. This separator paper was attached to the inner side (the side in contact with the foil sample) of a flat SUS plate sliding piece (projection size: □63 mm square) with a mass of 200 g connected to the force gauge via a soft SUS cable with a buffer spring, and the foil sample was fixed flatly on a horizontally set smooth acrylic plate with a thickness of 10 mm, and slid horizontally at a constant speed of 100 mm / min, and the load at this time was sampled every 60 milliseconds. The maximum load generated shortly after the sliding piece started to move was set as the maximum static friction force, and the average load in the stable motion state was set as the average dynamic friction force, and the static friction coefficient and the average dynamic friction coefficient were obtained by dividing them by the normal force (1.96 N) of the sliding piece. In Examples 2, 4, and 5, the friction force is improved by imparting a concavo-convex structure to the surface side of the first conductive layer, and compared with Comparative Example 1 in which the concavo-convex structure is not imparted to the surface side, it has been confirmed that both the static friction coefficient and the dynamic friction coefficient with the separator paper are greatly increased. In other words, it can be seen that by imparting a concavo-convex structure to the surface side of the first conductive layer, the adhesion with the solid electrolyte is improved, and in addition, a geometric structure suitable for retaining the solid electrolyte and the electrolyte can be obtained.

[0220] [Notes]

[0221] This disclosure discloses the following structures.

[0222] [Composition 1]

[0223] An electrode material having an oxide layer on a smooth substrate and further having an inorganic conductive layer on the oxide layer,

[0224] The inorganic conductive layer comprises: a first conductive layer containing a metal and / or a metal compound and a second conductive layer containing carbon.

[0225] The first conductive layer has a concave-convex portion on its surface side.

[0226] The second conductive layer is located at the outermost layer of the inorganic conductive layer.

[0227] [Composition 2]

[0228] In the electrode material according to configuration 1, the smooth substrate and the first conductive layer are made of different materials.

[0229] [Composition 3]

[0230] In the electrode material according to configuration 1 or 2, the second conductive layer is substantially composed of carbon.

[0231] [Composition 4]

[0232] In the electrode material described in any one of Configurations 1 to 3, the inorganic conductive layer further comprises a dense layer in which the metal and / or metal compound is densely present, and the dense layer is formed between the oxide layer and the first conductive layer.

[0233] [Composition 5]

[0234] An electrode material as described in any one of structures 1 to 4, wherein in the aforementioned inorganic conductive layer, both the aforementioned first conductive layer and the aforementioned second conductive layer or at least the aforementioned first conductive layer are composed of a particle deposition layer, and the aforementioned first conductive layer contains titanium, aluminum, and at least one of their nitrides, oxides, oxynitrides, carbides, and carbonitrides.

[0235] [Composition 6]

[0236] The electrode material according to any one of Configurations 1 to 5, wherein the oxide layer is an oxide layer containing phosphorus.

[0237] [Composition 7]

[0238] The electrode material according to any one of Configurations 1 to 6, wherein the smooth substrate contains aluminum or an aluminum alloy.

[0239] [Composition 8]

[0240] An electrode material as described in any one of structures 1 to 7, wherein the maximum current value of a cyclic voltammogram obtained by cyclic voltammetry under the conditions of a scanning range of ±0.3VvsPt, a scanning speed of 500mV / sec, an electrolyte at 30°C, a reference electrode Pt, a relative electrode stainless steel, and using the aforementioned electrode material as a working electrode, is at least 6.5 times the maximum current value of the cyclic voltammogram when the aforementioned smooth substrate is used as a working electrode under the aforementioned conditions.

[0241] [Composition 9]

[0242] An electrode material as described in any one of structures 1 to 8, wherein a mixed layer in which a substance constituting the first conductive layer and a substance constituting the second conductive layer are mixed is formed between the first conductive layer and the second conductive layer, and the composition of the mixed layer is as follows: as it moves from the first conductive layer toward the second conductive layer, the composition changes from a composition substantially containing only a substance constituting the first conductive layer to a composition substantially containing only a substance constituting the second conductive layer.

[0243] [Composition 10]

[0244] The electrode material as described in configuration 8, wherein a mixed layer in which a substance constituting the first conductive layer and a substance constituting the second conductive layer are mixed is formed between the first conductive layer and the second conductive layer, and the composition of the mixed layer changes from a composition substantially containing only the substance constituting the first conductive layer to a composition substantially containing only the substance constituting the second conductive layer as it moves from the first conductive layer toward the second conductive layer;

[0245] When analyzing the amount of each C bonding state from the surface of the second conductive layer toward the depth direction by XPS (X-ray photoelectron spectroscopy), the ratio of the amount of bonding between atoms of the metal element constituting the first conductive layer and carbon atoms is 5% or more relative to the total amount of each C bonding state shown by the C1s spectrum.

[0246] [Composition 11]

[0247] An electrode material as described in configuration 10, wherein, with respect to the half-width of the G band peak obtained by peak separation in a Raman spectrum formed by Raman spectroscopy, the half-width of the carbon contained in the second conductive layer is 3.8 times or more relative to the half-width of the graphite crystal.

[0248] [Composition 12]

[0249] In the electrode material according to Configuration 11, a substance constituting the first conductive layer and a substance constituting the second conductive layer are different from each other.

[0250] [Composition 13]

[0251] In the electrode material according to configuration 11 or 12, the BET specific surface area thereof using krypton (Kr) as an adsorbed gas is 1.5 times or more the BET specific surface area of ​​the smooth substrate.

[0252] [Composition 14]

[0253] In the electrode material according to Configuration 13, an average diameter of convex portions of the concavo-convex portion on the surface side of the inorganic conductive layer is 210 nm or less.

[0254] [Composition 15]

[0255] The electrode material according to any one of Configurations 1 to 14, wherein the carbon is graphite-like carbon. [Configuration 16]

[0256] For the electrode material described in any one of structures 1 to 15, the static friction coefficient and dynamic friction coefficient of the surface side surface relative to the separator paper are respectively higher than: the static friction coefficient and dynamic friction coefficient of the surface side surface of the electrode material having a conductive layer composed of carbon as the outermost layer on the surface side on a smooth substrate and no concave-convex parts on the surface side.

[0257] [Composition 17]

[0258] A cathode foil for an electrolytic capacitor, wherein at least a solid electrolyte is present between an anode foil and a cathode foil, and the electrode material described in any one of configurations 1 to 16 is used.

[0259] [Composition 18]

[0260] An electrolytic capacitor having at least a solid electrolyte between an anode foil and a cathode foil, and comprising the cathode foil of configuration 17.

[0261] [Composition 19]

[0262] In the electrolytic capacitor according to Configuration 18, an electrolyte solution is further present between the anode foil and the cathode foil.

[0263] [Industrial Applicability]

[0264] The electrode material of the present invention can be used as a cathode foil of an electrolytic capacitor such as a hybrid capacitor or a solid electrolytic capacitor. In addition, the electrode material of the present invention can be used in various capacitors, various power storage devices such as an electric double layer capacitor, a lithium ion capacitor, and a lithium ion battery, or various power generation elements such as a fuel cell, a solar cell, a thermal power generation element, and a vibration power generation element.

[0265] Description of Reference Numerals

[0266] 1 Cathode foil (electrode material)

[0267] 2. Substrate

[0268] 3 Oxide layer

[0269] 4 First conductive layer

[0270] 5 Second conductive layer

[0271] 6 Dense layer

[0272] 7 Mixed Layer

[0273] 8 Wound solid electrolytic capacitors, wound hybrid capacitors

[0274] 9 Anode foil

[0275] 10 Cathode foil

[0276] 11 Separator paper

[0277] 12 Capacitor elements

[0278] 13 Anode terminal

[0279] 14 Cathode terminal

[0280] 15 Aluminum housing

[0281] 16 Sealing rubber.

Claims

1. An electrode material having an oxide layer on a smooth substrate, and further having an inorganic conductive layer on the oxide layer, The inorganic conductive layer comprises: a first conductive layer containing metal and / or metal compound and a second conductive layer containing carbon. The first conductive layer has a concave-convex portion on its surface side, The second conductive layer is located at the outermost layer of the inorganic conductive layer.

2. The electrode material according to claim 1, wherein The smooth substrate and the first conductive layer are made of different materials.

3. The electrode material according to claim 1 or 2, wherein The second conductive layer is substantially composed of carbon.

4. The electrode material according to claim 1 or 2, wherein The inorganic conductive layer further includes a dense layer in which the metal and / or the metal compound is densely present, and the dense layer is formed between the oxide layer and the first conductive layer.

5. The electrode material according to claim 1 or 2, wherein In the inorganic conductive layer, both the first conductive layer and the second conductive layer or at least the first conductive layer are composed of a particle deposition layer, and the first conductive layer contains at least one of titanium, aluminum, and their nitrides, oxides, oxynitrides, carbides, and carbonitrides.

6. The electrode material according to claim 1 or 2, wherein The oxide layer is an oxide layer containing phosphorus.

7. The electrode material according to claim 1 or 2, wherein The smooth substrate contains aluminum or an aluminum alloy.

8. The electrode material according to claim 1, wherein The maximum current value of the cyclic voltammogram obtained by cyclic voltammetry under the conditions of a scan range of ±0.3VvsPt, a scan rate of 500mV / sec, an electrolyte at 30°C, a reference electrode of Pt, a relative electrode of stainless steel, and using the electrode material as the working electrode is more than 6.5 times the maximum current value of the cyclic voltammogram when the smooth substrate is used as the working electrode under the conditions.

9. The electrode material according to claim 1 or 2, wherein A mixed layer in which a substance constituting the first conductive layer and a substance constituting the second conductive layer are mixed is formed between the first conductive layer and the second conductive layer, and the composition of the mixed layer changes from a composition substantially containing only a substance constituting the first conductive layer to a composition substantially containing only a substance constituting the second conductive layer as it moves from the first conductive layer toward the second conductive layer.

10. The electrode material according to claim 8, wherein A mixed layer in which a substance constituting the first conductive layer and a substance constituting the second conductive layer are mixed is formed between the first conductive layer and the second conductive layer, and a composition of the mixed layer changes from a composition substantially containing only a substance constituting the first conductive layer to a composition substantially containing only a substance constituting the second conductive layer as it moves from the first conductive layer toward the second conductive layer; When analyzing the amount of each C bonding state from the surface of the second conductive layer toward the depth direction by X-ray photoelectron spectroscopy XPS, the ratio of the amount of bonding between atoms of the metal element constituting the first conductive layer and carbon atoms to the total amount of the C bonding states shown by the C1s spectrum is greater than 5%.

11. The electrode material according to claim 10, wherein Regarding the half-value width of a G band peak obtained by peak separation in a Raman spectrum formed by Raman spectroscopy, the half-value width of carbon contained in the second conductive layer is 3.8 times or more relative to the half-value width of graphite crystal.

12. The electrode material according to claim 11, wherein A material constituting the first conductive layer and a material constituting the second conductive layer are different from each other. 13 . The electrode material according to claim 11 , wherein the BET specific surface area of ​​the electrode material using krypton gas Kr as an adsorbed gas is 1.5 times or more the BET specific surface area of ​​the smooth substrate.

14. The electrode material according to claim 13, wherein The average diameter of the convex parts of the concavo-convex part on the surface side of the inorganic conductive layer is 210 nm or less.

15. The electrode material according to claim 1 or 2, wherein The carbon is graphite-like carbon.

16. The electrode material according to claim 1 or 2, wherein the static friction coefficient and dynamic friction coefficient of the surface side of the electrode material relative to the separator paper are respectively higher than the static friction coefficient and dynamic friction coefficient of the surface side of the electrode material relative to the separator paper, which has a conductive layer composed of carbon as the outermost layer on the surface side on a smooth substrate and has no concave-convex parts on the surface side. 17 . A cathode foil for an electrolytic capacitor, wherein at least a solid electrolyte is present between an anode foil and a cathode foil, wherein the electrode material according to claim 1 or 2 is used. 18 . An electrolytic capacitor having at least a solid electrolyte between an anode foil and a cathode foil, the electrolytic capacitor comprising the cathode foil for an electrolytic capacitor according to claim 17 .

19. The electrolytic capacitor according to claim 18, wherein: There is also an electrolyte between the anode foil and the cathode foil.

Citation Information

Patent Citations

  • Electrode body, electrolytic capacitor provided with electrode body, and method for producing electrode body

    EP3817020A1

  • Ion conductive material and ionic matter

    JP2004281223A

  • Process for manufacturing solid electrolytic capacitor

    JP2005294500A

  • Electrolyte capacitor and manufacturing method thereof

    JP2006190878A

  • Wet electrolytic capacitor

    JP2007243203A